Language attitudes and language shift among ethnic migrants in Khartoum - Mugaddam, Abdel Rahim Hamid (AAeO - Afrikanistik-Aegyptologie-Online, 2005)
This paper investigates language attitudes among ethnic migrant groups in Khartoum, the capital city of Sudan. A questionnaire was used to collect data on language preference, language parents prefer their children to learn, and reasons for language preference. Results suggest that while positive attitude played a significant role in learning Arabic among some of the groups under investigation, it proved to be of no help in maintaining the groups’ ethnic languages. Arabic was reported as very important for education, religious activities, economic privileges and social interaction. Ethnic languages, on the other hand, were preferred for purely symbolic reasons (symbolizing groups’ ethnic identity).